2020
DOI: 10.1002/ddr.21670
|View full text |Cite
|
Sign up to set email alerts
|

Antiurolithiatic effects of pentacyclic triterpenes: The distance traveled from therapeutic aspects

Abstract: Globally, approximately 12% of the population is inflicted by various types of urolithiasis. Standard treatments are available both to avert and treat urolithiasis, but with significant adverse side effects. Pentacyclic triterpenes represent a group of naturally occurring compounds which holds immense potential as therapeutic for treating kidney stone. This review aims to provide an integrative description on how pentacyclic triterpenes can effectively treat calcium oxalate urolithiasis through various mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 129 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…Citrate is a compound that can inhibit crystal deposition and growth in renal tissue [ 74 , 75 , 76 ]. Additionally, these types of compounds stimulate the relaxation of the smooth muscle of the urothelium, which promotes a decrease in their size and facilitates expulsion of the urinary stones [ 77 ].…”
Section: Molecular Mechanism Of Bioactive Compounds Present In Medici...mentioning
confidence: 99%
“…Citrate is a compound that can inhibit crystal deposition and growth in renal tissue [ 74 , 75 , 76 ]. Additionally, these types of compounds stimulate the relaxation of the smooth muscle of the urothelium, which promotes a decrease in their size and facilitates expulsion of the urinary stones [ 77 ].…”
Section: Molecular Mechanism Of Bioactive Compounds Present In Medici...mentioning
confidence: 99%
“…as lithotriptic agent. Phytomolecules like Kaempferol and kaempferol analogs ( Cechinel-Zanchett et al, 2020 ), Quercetin and quercetin analogs ( Dinnimath et al, 2017 ), Stigmasterol ( Lobine et al, 2020 ), and Ferulic acid ( Zhao et al, 2019 ) which were previously been reported from Alternanthera sessilis (L.) R.Br. ex DC., may be responsible for this antiurolithiatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has become very clear that, considering their very large plethora of biologic effects, triterpenic acids presumably act on multiple pathways; indeed, there are many reviews published in the past 10 years regarding their mechanism of action responsible for various activities, such as anticancer [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], immunomodulatory [ 23 , 24 ], antidiabetic [ 25 , 26 , 27 , 28 , 29 , 30 ], anti-inflammatory [ 31 ], cardioprotective [ 32 ], antiurolithic [ 33 ], antiviral [ 34 ], and wound healing [ 35 , 36 ]. This review aims to summarize the most recent (last five years) discoveries on triterpenic acids’ mechanisms of action in order to provide scientists with exhaustive knowledge, which in turn might propel and diversify future studies.…”
Section: Introductionmentioning
confidence: 99%